2022
DOI: 10.1186/s13019-022-01992-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperbilirubinemia associated acute kidney injury on chronic kidney disease after aortic arch surgery: a retrospective study with follow-up of 1-year

Abstract: Background Hyperbilirubinemia (HB) is a serious complication in aortic arch surgery, which is associated with acute kidney injury (AKI). The association between HB and chronic kidney disease (CKD) is unknown. The aim of this study was to investigate the impact of HB associated AKI on CKD after aortic arch surgery. Methods We reviewed 284 patients who underwent aortic arch surgery from 2016 to 2020 in our hospital. AKI was defined as a 50% increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The systemic inflammatory response, hemolysis and hepatic hypoperfusion caused by cardiopulmonary bypass, and high volumes of blood products may disrupt the bilirubin metabolism and lead to hyperbilirubinemia (4). Our previous study showed that patients suffering from hyperbilirubinemia associated AKI were at more increased odds of CKD after aortic arch surgery (5). Although bilirubin is an endogenous antioxidant with renal protection function (6), abnormally high concentrations of bilirubin could induce oxidative stress and cell apoptosis, which are associated with neurological dysfunctions (7), respiratory failure (8), and thrombocytopenia (9).…”
Section: Introductionmentioning
confidence: 99%
“…The systemic inflammatory response, hemolysis and hepatic hypoperfusion caused by cardiopulmonary bypass, and high volumes of blood products may disrupt the bilirubin metabolism and lead to hyperbilirubinemia (4). Our previous study showed that patients suffering from hyperbilirubinemia associated AKI were at more increased odds of CKD after aortic arch surgery (5). Although bilirubin is an endogenous antioxidant with renal protection function (6), abnormally high concentrations of bilirubin could induce oxidative stress and cell apoptosis, which are associated with neurological dysfunctions (7), respiratory failure (8), and thrombocytopenia (9).…”
Section: Introductionmentioning
confidence: 99%